Sub-districts as Sub-district Apparatus in the Implementation of Government According to Law 23 of 2014 - Ida Surya (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
The Village Government in the era of Regional autonomy has undergone many changes along with the changing paradigm of government as mandated in Law Number 23 of 2014 concerning Regional Government and Government Regulation Number 73 of 2005 concerning Villages. The purpose of Village structuring and government implementation in the era of Regional Autonomy is to improve coordination of government administration, public services, implementing development, and empowering Village/Sub-district communities. The method used is an empirical research method with a legislative study approach and a conceptual and sociological approach. The data analysis used is the method of interpretation of legislation and authentic interpretation. The expected result is that the Village government is required to be open to the community, both regarding development programs and the budget obtained, so that there is high trust in the Village government from the community, thus realizing the vision and mission of the village. All public services and civil services that were previously conventional are now required to be technology-based. The Village Head, as the head of government at the Village level, and other government units, including the Technical Implementation Unit, should collaborate and coordinate in all sectors by empowering the community so that a just, prosperous, and equitable society is realized.